2019
DOI: 10.1083/jcb.201808091
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B3 promotes anaphase I onset in oocyte meiosis

Abstract: Meiosis poses unique challenges because two rounds of chromosome segregation must be executed without intervening DNA replication. Mammalian cells express numerous temporally regulated cyclins, but how these proteins collaborate to control meiosis remains poorly understood. Here, we show that female mice genetically ablated for cyclin B3 are viable—indicating that the protein is dispensable for mitotic divisions—but are sterile. Mutant oocytes appear normal until metaphase I but then display a highly penetrant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 76 publications
(121 reference statements)
4
76
0
3
Order By: Relevance
“…To assess whether degradation of securin and cyclin B1 in prometaphase caused separase activation, we used a separase activity biosensor generated by Nam et al that has previously been validated in oocytes 3739 . The sensor consists of nucleosome-targeted H2B protein fused to eGFP and mCherry fluorophores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether degradation of securin and cyclin B1 in prometaphase caused separase activation, we used a separase activity biosensor generated by Nam et al that has previously been validated in oocytes 3739 . The sensor consists of nucleosome-targeted H2B protein fused to eGFP and mCherry fluorophores.…”
Section: Resultsmentioning
confidence: 99%
“…However we suggest that, similar to other prometaphase APC/C substrates, this region of securin could be involved in either direct binding to the APC/C or in outcompeting spindle assembly checkpoint protein inhibition of APC/C-Cdc20 4750 . In addition, cyclin B3 has recently been shown to have an important role in mouse oocyte MI in priming the APC/C for securin and cyclin B1 destruction 39,51,52 . Therefore an alternative possibility is that this region in securin is regulated by cyclin B3 and involved in an oocyte-specific APC/C activation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Despite prominent, regulated expression during spermatogenesis, Ccnb3-deficient males are fully fertile and exhibit no gross meiotic abnormalities. While we cannot exclude the possibility that the em1 allele retains partial Ccnb3 function, our molecular characterization of mRNA and protein expression in testes (this study) and the strong metaphase I arrest in homozygous mutant oocytes (Karasu et al 2019) show that this allele is at least a substantial loss-of-function mutation. Furthermore, an independently generated Ccnb3 mutation that similarly causes oocyte arrest was also reported to support normal male fertility .…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, in mouse oocytes, silencing Mad2 does not rescue the meiotic metaphase arrest upon Cyclin B3 depletion (Zhang et al, 2015a). In other studies, SAC markers on kinetochores did not persist in metaphase-arrested Ccnb3 KO oocytes, and SAC inactivation by chemical inhibition of Mps1 did not restore anaphase (Karasu et al, 2019;Li et al, 2019b).…”
Section: Introductionmentioning
confidence: 76%
“…Based on results obtained in flies and mice, it has been suggested that CycB3 may function upstream of the APC/C to activate it (Karasu et al, 2019;Li et al, 2019b;Yuan and O'Farrell, 2015;Zhang et al, 2015a). We decided to test this hypothesis.…”
Section: Cycb3 Functions Upstream Of the Apc/c And Collaborates With mentioning
confidence: 99%